Effects of theta-binaural beats auditory stimulation on creativity, psychological well-being and mood states of university students: Pilot study - Mendes, Liliana; Leonido, Levi; Pereira, Antonino; Morgado, Elsa Gabriel (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of theta-frequency binaural beats (BB) on creativity, mood, and psychological well-being in university students, addressing the growing interest and controversy surrounding this auditory stimulation technique. A quantitative, correlational, quasi-experimental design was employed, involving 26 university students aged 18–54 (96.2% female, 3.8% male). Participants listened to theta BB (6-Hz beat frequency on a 250 Hz carrier) for 20 minutes daily using the Binaural Beats App. Instruments included a sociodemographic questionnaire, the reduced Creative Personality Scale (EPC), the short Profile of Mood States Questionnaire (POMS), and the Psychological Well-Being Manifestation Scale (EMMBEP). Results revealed significant improvements in creativity, psychological well-being, and reduced total mood disturbance after exposure to theta BB. Significant differences in total mood disturbance across assessment moments highlighted the intervention’s time-sensitive benefits. The study highlights the potential of theta-frequency BB to enhance psychological well-being, mood, and creativity among university students. These findings contribute to the growing body of evidence supporting the utility of BB as a non-invasive tool for improving mental and emotional states. Theta BB may serve as an accessible and cost-effective method for promoting mental health and fostering creativity in educational and therapeutic settings.